Surface modification of nylon 6 by 50 Hz dielectric barrier discharge Produced in air and argon at atmospheric pressure (BIBECHANA, 2023)
This paper reports the use of dielectric barrier discharge (15.65 kV, 50 Hz) produced in an air and argon environment at atmospheric pressure to modify the surface of Nylon 6. Power dissipation in air and argon DBD was determined to be 14.60 W and 12.00 W, respectively. Similarly, the average density and temperature of an electron in air DBD were found to be 1.74 ×1011 cm-3 and 1.31 eV, respectively, while the values were 2.50 ×1011 cm-3 and 0.68 eV in argon DBD. The water contact angle (WCA) was measured to confirm the enhancement in wettability. On treating the sample with air DBD for 15 minutes, the contact angle reduced from 134.07° ± 3.20° to 89.11° ± 3.06° while it was reduced to 82.74° ± 4.20° within 1 minute using argon. The study found that treating a hydrophobic sample of Nylon 6 with DBD for a certain period of time transformed it into a hydrophilic one, and extending the treatment time further enhanced its wettability. The use of argon DBD was found to be more effective than air DBD in altering the surface properties of the sample, as the sample became hydrophilic after only one minute of treatment with argon DBD and completely wettable after three minutes. The findings suggest that air and argon DBD have potential applications in modifying the surface properties of Nylon 6, which could have practical implications in the production of textiles, membranes, and other materials.